Analysis of organizational Internal factors influencing construction risk management among construction industries - Omer, Manal Suliman; M.N., M. Nawi; Adeleke, A. Q.; Sitansu, Panda; A. N., Harun; Salameh, Anas A. (GITO Verlag, P, 2021)
Many previously conducted empirical studies have displayed mixed findings about the influence of internal factors within an organization on the management of risk among construction companies. Hence, there is a need for introducing a moderating variable to this field of study. The aim of this research was to confirm whether coercive pressure plays a significant role in the relationship between the management of risk in construction and factors within the organization. Therefore, this study examined the influence that internal organizational factors and coercive pressure have on the management of construction risk through the lens of discouragement and organizational control theory, and institutional theory. Data were collected through the distribution of questionnaires involving 165 workers working in the Malaysian Peninsular construction companies, and the analysis was performed by means of partial least squares structural equation modelling. Results revealed a positively significant connection between internal organizational factors and the management of construction risk. Also, coercive pressure and the management of construction risk has a positively significant relationship. Coercive pressure mediated the connection that organizational internal factors had with the management of construction risk. A discussion of the research implications was done from the point of view of Malaysia. In conclusion, the reduction of risk incidents in the process of carrying out construction activities is being facilitated by active leadership and organizational culture. In addition, the rate and period at which accidents occur during and after the completion of construction activities are reduced by coercive pressure. In the same way, some influential internal factors of organizations as well as the introduced coercive pressure in the process of managing construction risk have established that many construction companies that apply the necessary internal factors as well as the coercive pressure introduced by the government are able to make delivery of their construction task at the specified cost, time, and qualities, thus establishing them as the correct standard for measuring a well-constructed project.